Neither Here Nor There: Borrowed Bodies, Third Space, and the Museum - Rebecca DiGiovanna (Pursuit - The Journal of Undergraduate Research at the University of Tennessee, 2015)
The contemporary art world is in a state of great influx and change. In part due to globalization, the arts are producing works that no longer adhere to a dichotomy of male vs. female, black vs. white, Asian vs. American, and so forth. Instead, artists are intermingling these seemingly separate identities into new forms of categorization and selfhood. Using expat artist Zhang Huan’s My America as a vehicle for discussion, this essay examines Chinese post-colonial philosopher Homi Bhabha’s Third Space of Enunciation and its relationship to the rising multiplicity of identity seen in contemporary artists. An argument is made for the need to transform and reinvent the way modern museums deal with cultural ancestry, geography, and the increasing diversity of both artists and the museum audience.